Engineering Research Methodology A Practical Insight for Researchers - Deb, Dipankar; Dey, Rajeeb; Balas, Valentina E. (Intelligent Systems Reference Library,, 2019)
The book covers all the important aspects of research methodology, and addresses the specific requirements of engineering students, such as methods and tools, in detail. It also discusses effective research in engineering today, which requires the ability to undertake literature reviews utilizing different online databases, to attribute credit for any prior work mentioned, to respect intellectual property rights while simultaneously maintaining ethics in research, and much more. Further, the book also considers soft skills like research management and planning, dealing with criticism in research and presentation skills, which are all equally important and need to include in research methodology education. Lastly, it provides the technical knowhow needed to file patents in academia, an important area that is often ignored in research methodology books. The book is a particularly valuable resource for PhD students in India and South East Asia, as research methodology is a part of their coursework.